Neurophysiological Examinations as Adjunctive Tool to Imaging Techniques in Spontaneous Intracerebral Hemorrhage: IRONHEART Study - Fekete, Klára; Tóth, Judit; Horváth, László; Márton, Sándor; Héja, Máté; Csiba, László; Árokszállási, Tamás; Bagoly, Zsuzsa; Sulina, Dóra; Fekete, István (Frontiers in Neurology, 2021)
Introduction: Intracerebral haemorrhage (ICH) is a devastating disease, which may lead to severe disability or even death. Although many factors may influence the outcome, neurophysiological examinations might also play a role in its course. Our aim was to examine whether the findings of electroencephalography (EEG) and transcranial magnetic stimulation (TMS) can predict the prognosis of these patients. Methods: Between 1 June 2017 and 15 June 2021, 116 consecutive patients with ICH were enrolled prospectively in our observational study. Clinical examinations and non-contrast computerized tomography (NCCT) scan were done on admission for ICH, follow-up NCCT scans were taken at 14 ± 2 days and at 3 months ± 7 days after stroke onset. EEG and TMS examinations were also carried out. Results: 65.5% of the patients were male, and the mean age of the study population was 70 years. Most patients had a history of hypertension, 50.8% of which had been untreated. In almost 20% of the cases, excessive hypertension was measured on admission, accompanied with >10mmol/L blood glucose level, while their GCS was 12 on average. Presence of blood in the ventricles or subarachnoid space, high blood and perihaematomal volumes meant poor prognosis. Pathological EEG was prognostic of a worse outcome. With TMS examination at 14 days it might be possible to estimate outcome in a univariate model and the absence or reduction of the amplitude of the motor evoked potentials was associated with poor prognosis. Conclusion: Together with the clinical symptoms, the volume of bleeding, perihaematomal oedema (or their combined volume), and neurophysiological examinations like EEG and TMS play an important role in the neurophysiological outcome of patients with ICH. This might affect the patients’ rehabilitation plans in the future, since with the help of the examinations a possibly recovering group could be selected.